2011
DOI: 10.3390/molecules16053802
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Oriented Synthesis Based on the DPPP-Catalyzed Mixed Double-Michael Reactions of Electron-Deficient Acetylenes and β-Amino Alcohols

Abstract: In this study, we prepared oxizolidines through 1,3-bis(diphenylphosphino)-propane (DPPP)–catalyzed mixed double-Michael reactions of β-amino alcohols with electron-deficient acetylenes. These reactions are very suitable for the diversity-oriented parallel syntheses of oxizolidines because: (i) they are performed under mild metal-free conditions and (ii) the products are isolated without complicated work-up. To demonstrate the applicability of mixed double-Michael reactions for the preparation of five-membered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Kwon and Sriramurthy reported the first examples of mixed double-Michael reactions, allowing access to highly functionalized oxazolidines, thiazolidines, and pyrrolidines with excellent efficiencies and diastereoselectivities. 56 Using di-nucleophiles derived from L-amino acids, the annulation products were obtained in enantiomerically pure form (Scheme 63). The use of 1,3-bis(diphenylphosphino)propane is critical, providing anchimeric assistance in stabilizing the reaction intermediates.…”
Section: Phosphine Catalysis Of Alkynesmentioning
confidence: 99%
“…Kwon and Sriramurthy reported the first examples of mixed double-Michael reactions, allowing access to highly functionalized oxazolidines, thiazolidines, and pyrrolidines with excellent efficiencies and diastereoselectivities. 56 Using di-nucleophiles derived from L-amino acids, the annulation products were obtained in enantiomerically pure form (Scheme 63). The use of 1,3-bis(diphenylphosphino)propane is critical, providing anchimeric assistance in stabilizing the reaction intermediates.…”
Section: Phosphine Catalysis Of Alkynesmentioning
confidence: 99%
“…In 2011, the same authors expanded the scope of this methodology synthesizing sixty different chiral heterocycles. 86 Using the same strategy, Kwon and co-workers have also prepared seven different types of benzannulated N-heterocycles 164 in a one-step process in excellent yields. In some cases, it was necessary to use acetic acid and sodium acetate as additives to expedite efficient proton transfer steps (Scheme 73).…”
Section: Reactions Of Alkynes With Di-nucleophilesmentioning
confidence: 96%
“…In 2007, we reported a phosphine-catalyzed double-Michael addition in which a bisphosphine was the best catalyst [23-25]. We suggested that anchimeric assistance by the other tethered phosphino group stabilized the resultant phosphonium cation in the transitional intermediates, leading to a higher yield of the double-Michael adduct.…”
Section: Introductionmentioning
confidence: 99%